Effect of Minicutting Length and Leaf Area Reduction on Growth and Nutritional Status of Eucalypt Propagules. (17th July 2013) - Santana, Reynaldo Campos; Fernandes, Sula Janaina Oliveira; Titon, Miranda; Xavier, Aloisio; de Souza, Priscila Fernandes; Barros Filho, Nairam Felix
Abstract : Significant improvements to the technique of minicutting Eucalyptus clones have been reported in the literature. However, despite these recent efforts, studies addressing the proper size of minicuttings and the reduction of leaf area have not been well explored. Thus, the present study had the objective of evaluating the effects of the length of the minicuttings and the leaf area reduction on the growth and nutritional condition of Eucalyptus urophylla during propagation. The experiment was conducted for 90 days in the Plantar Reforestation Co. Nursery in the municipality of Curvelo, MG, using a randomized block design with 4 replicates in a4 × 2 × 2 factorial arrangement. The effects of 4 lengths of minicuttings (4, 6, 8, and 10 cm), 2 levels of leaf area reductions (0 and 50%), and 2 commercial clones were studied. The length of the minicuttings and the reduction of leaf area did not affect the nutritional status of the leaves, nor did the length affect the quality of the plants at the age of 90 days. The results indicate that it is unnecessary to reduce the leaf area for Eucalyptus propagation.